Representing Distinguished Doctors - Williams, Preston L.; Williams, Joanna P. (British Journal of Healthcare and Medical Research, 2023)
Convention in many US states asserts the predominating myth that only physicians can be called doctors. However, even the core of the word “doctor” being “docere,” translates into “to teach,” thus capturing the full breadth of professionals and returning the title to its rightful honorary collective of doctoral-trained professionals. With the dawn of tighter legal restrictions imposed by state entities, current written laws forbid the use of the word “doctor” by making it synonymous only with physicians. Effectively, this monopolizes the term “doctor” and consequently excludes other highly qualified doctoral-trained professionals, likely infringing on their constitutional rights. Presently, there is a great deal of discourse between the medical and legal professions regarding the merits of such a matter, and this paper aims to discuss some of the salient points to provide more clarity in the use of the title “doctor” for all doctoral-trained professionals who would stand to face occupational or legal repercussions in instances where the title would be exercised. The goal is for an equitable professional representation by title, returning an expropriated term to those who have achieved professional doctoral training and expertise.